Smaller babies at risk: birth weight impacts neonatal survival status in Silte zone, Central Ethiopia. A survival analysis of prospective cohort study - Jemal, Musa; Kemal, Abdurezak; Mohammed, Bekri; Bedru, Delwana; Kedir, Shemsu (Frontiers in Pediatrics, 2024)
Introduction Globally, 2.4 million neonates died in their first month of life in 2019 with approximately 6,700 neonatal deaths every day. Ethiopia is 4th among the top 10 countries with the highest number of neonatal deaths. Yet, there are few prospective studies on neonatal mortality in the central region of Ethiopia. Hence, to develop evidence-based, locally tailored intervention strategies, it is necessary to evaluate neonatal survival status and mortality predictors, including birth weight. Therefore, the current study aims to assess survival status and factors predicting the survival of neonates in the Silt’e zone, Ethiopia. Methods An institution-based prospective cohort study design was employed from 1 May to 30 July 2022. Data were collected from term neonates who were enrolled according to their order of health facility visit and then followed by data collectors in their homes. Data were analyzed using STATA version 14.1. Neonatal survival was presented using the Kaplan–Meier survival curve. The crude and adjusted associations were evaluated using the Cox proportional-hazards model, presented with a 95% confidence interval (CI), and a P-value <0.05 was used to declare statistical significance. Result In total, 1,080 term neonates were followed for a total of 27,643.6 neonatal days. The study showed a 95% cumulative probability of surviving the neonatal period. The incidence rate of neonatal death was 2.02 per 1,000 neonatal days. Maternal history of neonatal death [adjusted hazard ratio (AHR) = 4.03; 95% CI: 2.28–9.52], complication during pregnancy (AHR = 3.08; 95% CI: 1.12–8.25), female sex (AHR = 0.45; 95% CI: 0.25–0.84), birth weight (AHR = 0.27; 95% CI: 0.11–0.63), and a low or intermediate APGAR score at 1 min (AHR = 3.11; 95% CI: 1.23–7.82 and AHR = 5.34; 95% CI: 1.63–17.51, respectively) were independent predictors of neonatal death. Conclusion It has been noted that neonatal mortality in this area is higher than results from national studies and other study areas and thus requires strict attention and interventions targeting both the pre and postnatal periods. Babies with low birth weight were found to struggle to survive the neonatal period. Promoting maternal nutrition for normal birth weight of the newborn would thereby improve neonatal survival, and should be followed as a strategy.